Penataan Ruang Kawasan Perkotaan Denpasar-Badung-Gianyar-Tabanan (Sarbagita) Provinsi Bali dalam Perspektif Otonomi Daerah & Hak Asasi Manusia - Allan Fatchan Gani Wardhana; Diva Febrina Nurcahyani Rahman (Fakultas Hukum Universitas Islam Indonesia, 2023)
This research will examine the spatial planning policies of the Denpasar-Badung-Gianyar-Tabanan (Sarbagita) Urban Area with the perspective of regional autonomy and human rights. Two things will be studied, namely first, the concept of spatial planning in the Denpasar-Badung-Gianyar-Tabanan (Sarbagita) Urban Area of Bali Province, secondly, related to whether the urban spatial planning is in line with the concept of regional autonomy and correlates with the principles of human rights. The research method used is normative juridical with statutory and conceptual approaches. The results of the study concluded that first, the formation of regulations regarding the Sarbagita Urban Area is dominated by the Central Government, while the Regional Government only follows the policies of the Central Government. As for the management aspect of the Sarbagita urban area, management is carried out by the Minister, Governor, and Regent or Mayor in accordance with their authority. Second, the development and management of urban areas must pay attention to the principles of human rights, one of which is to provide opportunities for the community to be involved in the arrangement, management and utilization of the spatial planning of the Sarbagita urban area.